Multilayer phosphor-in-glass packaging for the development in WLED color uniformity - Huu Phuc Dang; Phung Ton That; Tri-Vien Vu (Universitas Ahmad Dahlan, 2021)
When mentioning the remote phosphor structure, the most noticeable advantage is its higher luminous flux than any other structure’s. However, there are existing flaws in their color uniformity and color rendering index (CRI). Thus, the improvements in these two optic factors must be improved for the better usage of remote phosphor geometry in modern WLED devices. Many researchers have drawn their attention to this idea, and then it has become the primary objective for their studies. In this paper, we also try to accomplish the same result by adjusting the distances between the phosphor layers and through that enhance the optical properties of WLEDs. The mie-scattering theory is applied in our calculations to ensure the reliability and accuracy of experimental results. In our research, with distance d = 0.64 mm, the luminous flux grew 9.7% in comparison to the original value. At 0.84 mm, the distance d enhanced the color uniformity by two times. In the meantime, the CRI remained static during the course of experiment. With suitable application, these results can bring valuable contributions to the development of next WELDs generation.